Leveraging Structural Changes in an Electronic Health Record Tool to Standardize Written Handoff. (July 2019) - Zavodnick, Jillian; Jaffe, Rebecca; Altshuler, Marc; Cowan, Scott; Wickersham, Alexis; Diemer, Gretchen
Miscommunications during patient handoff can lead to harm. The I-PASS bundle has been shown to improve safety outcomes. Although effective training reliably improves verbal handoffs, research has demonstrated a lack of effect on written handoffs. The objective was to compare written handoff before and after integration of a standardized electronic health record (EHR) tool. Interns at a large urban academic medical center underwent I-PASS handoff training. The EHR handoff tool was then revised to prompt the I-PASS components. Handoff documents were obtained before and after the intervention. More handoffs included Illness Severity (33% to 59%, P < .001) and Action List (65% to 83%, P = .005) after the intervention. There was no change in handoffs with miscommunications (12.5% to 10%, P = .566) or omissions (8% to 11%, P = .447). Handoffs including tangential or unrelated information decreased (20% to 4%, P = .001). A written handoff tool can reinforce the effect of training and increase adherence to I-PASS.